Fabricating mechanically improved silk-based vascular grafts by solution control of the gel-spinning process. (February 2020) - Rodriguez, Maria; Kluge, Jonathan A.; Smoot, Daniel; Kluge, Matthew A.; Schmidt, Daniel F.; Paetsch, Christopher R.; Kim, Peter S.; Kaplan, David L.
Abstract: There is a large unmet need for off-the-shelf biomaterial options to supplant venous autografts in bypass and reconstructive surgical procedures. Existing graft alternatives formed from non-degradable synthetic polymers are not capable of maintaining long-term patency and are thus not indicated for <6 mm inner diameter bypass procedures. To fill this void, degradable silk-based biomaterials have been proposed that can maintain their mechanical properties (i.e. compliance) while facilitating slow but progressive biomaterial remodeling and host integration mediated by cellular colonization. The goal of the present study was to enhance the porosity of gel-spun silk tubes, to facilitate faster degradation rates and improve cellularity, and thus improve host integration over time in vivo, while maintaining requisite mechanical functions. Silk solutions with a range of molecular weight distributions and, in turn, viscosities were used to generate tubes of varying porosities. A decrease in solution concentration correlated with an increase in mean pore size and overall porosity through a density-dependent mechanism. Tubes were mechanically analyzed, and these properties were the basis of an analytical model used to correlate tube formulations to structural compliance, which were shown to be similar to the saphenous vein. Tubes were also tested for suture retention to ensure surgical utility despite increased porosity. Tubes were implanted in the abdominal aorta of Sprague-Dawley rats via an end-to-end anastomosis model. Tubes with higher porosities showed early improvements in cell colonization that progressively increased over time; conversely, the dense architecture of less porous grafts (20MB) inhibited cell ingrowth and resulted in minimal biomaterial degradation at the 6-month time point. None of the highly porous tubes (5 MB and 10MB) remained patent at 6 months, likely due remodeling inducing bulk mechanical failure or a compromised blood-material interface.